Spatial Statistical Representation of the Population Density of Salah al-Din Governorate - Hasan, Ahmed Abdulsalam; Jassim, Sedeeq Mustafa (Journal of Tikrit University for Humanities, 2024)
The study aims to have an effective cartographic representation characterized by comprehensiveness, accuracy and objectivity in the representation of population data (Population density), and it aims at identifying the efficiency of cartographic visualization of maps of the study area using spatial statistical representation methods. The study started from the hypotheses and objectives that can be achieved using spatial statistical representation techniques. The study reached to a set of conclusions, including the modern technologies represented by spatial statistical cartographic representation methods have a major role in drawing and producing population maps with a high level of cartographic representation, as well as the ability to give a clear and close-to-reality picture of the nature of the spatial distribution of population data. The spatial statistical cartographic representation methods are characterized by a high visual perception in the numbers of population maps, as the aim of using more than one statistical representation method is to choose the best and most appropriate one in representing and preparing population maps. There is a need to explore data through histograms, distribution direction, and spatial autocorrelation before cartographic representation using spatial statistical representation method Kriging in order to know the nature of data distribution, spatial trends, and their correlations. The study proves that cartographic visualization has an important role in understanding and perceiving population maps using spatial statistical representation methods, as cartographic visualization is an important means of delivering information to its reader and user in a perceptive and understandable manner.